(untitled) (CIPEEX, 2022)
ACCORDING TO FLECK (1999), THE GROWING CONCERN WITH QUESTIONS RELATED TO QUALITY OF LIFE COMES FROM A MOVEMENT WITHIN THE HUMAN AND BIOLOGICAL SCIENCES IN ORDER TO VALUE PARAMETERS BROADER THAN THE CONTROL OF SYMPTOMS, THE REDUCTION OF MORTALITY OR THE INCREASE OF THE EXPECTATION OF LIFE. FOR THE WORLD HEALTH ORGANIZATION QUALITY OF LIFE IS THE INDIVIDUAL’S PERCEPTION OF THEIR POSITION IN LIFE IN THE CONTEXT OF THE CULTURE AND VALUE SYSTEMS IN WHICH THEY LIVE AND IN RELATION TO THEIR GOALS, EXPECTATIONS, STANDARDS AND CONCERNS. THE PERCEPTION OR SENSATION OF HAPPINESS ARE OFTEN EXPERIENCED BY SITUATIONS THAT REMIND US OF THE MEMORIES OF OUR ORIGINS, OFTEN SIMPLE AND HUMBLE. FROM THIS THEME WAS PERFORMED A MUSICAL PRESENTATION WITH PIANO, VIOLINS, GUITAR AND VOICES OF THE SONG FELICIDADE BY THE BRAZILIAN COMPOSER MARCELO JENECI. THROUGH SOME OF HIS VERSES: "... YOU WILL LAUGH, WITHOUT REALIZING, HAPPINESS IS JUST A MATTER OF BEING. WHEN IT RAINS, LET IT GET WET, TO GET THE SUN WHEN IT COMES BACK. BETTER LIVE, BABY, ’CAUSE THERE’S A PLACE WHERE THE SUN SHINES FOR YOU. CRYING, SMILING TOO AND THEN DANCING, IN THE RAIN WHEN THE RAIN COMES ... "IT WAS POSSIBLE TO ASSOCIATE THE HABITS OF A SMALL TOWN IN THE INTERIOR, LIKE SO MANY OTHERS IN BRAZIL. THE MOMENTS AND SMALL DETAILS THAT COMPOSE LIFE IN THOSE PLACES WHERE THERE SEEMS TO BE MORE TIME TO CONTEMPLATE THE DAYS OF A SIMPLE, SINCERE AND HAPPY LIFE.KEY WORDS: LIFE EXPECTANCY. QUALITY OF LIFE. HAPPINESS.